2016
DOI: 10.1177/1096348014525631
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of the Customer Participation Scale

Abstract: Although the importance of a mandatory customer participation construct in service delivery has been much discussed in the literature, little research has been devoted to conceptualizing and measuring one. To fill this void, this study followed a seven-step process for creating and analyzing scales in order to develop a customer participation scale and evaluate its generalizability, reliability, and validity. In theoretical terms, this scale extends the service quality literature, which has heavily emphasized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 39 publications
3
44
2
4
Order By: Relevance
“…Furthermore, the consumers' citizenship behaviour has a positive significant impact on the consumer value (β=0.31). The importance of purchase from intrinsic factors which influence the consumers' mandatory participation was examined in case of restaurant service and the authors found a direct positive impact on the information (β=0.16) and actionable (β=0.17) participation (Chen & Raab, 2014). This result is consistent with the statement that the purchase involvement of the consumers motivates to have further information searching and more active participation in service production (Hollebeek, Jaeger, Brodie, & Balemi, 2007).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the consumers' citizenship behaviour has a positive significant impact on the consumer value (β=0.31). The importance of purchase from intrinsic factors which influence the consumers' mandatory participation was examined in case of restaurant service and the authors found a direct positive impact on the information (β=0.16) and actionable (β=0.17) participation (Chen & Raab, 2014). This result is consistent with the statement that the purchase involvement of the consumers motivates to have further information searching and more active participation in service production (Hollebeek, Jaeger, Brodie, & Balemi, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…In a conceptual paper, the authors divide the value co-creation into six dimensions or types of actions performed by users and providers (Neghina, Caniëls, Bloemer & Van Birgelen, 2014). Regarding the research paper, Randall, Gravier & Prybutok (2011), Mc-Coll Kennedy, Vargo, Dagger, Sweeney & Van Kasteren, (2012), Yi & Gong (2013) and Chen & Raab (2014) are particularly relevant. The first study (Randall, Gravier & Prybutok, 2011) proposes the construction of a measurement scale composed of three dimensions: connection, trust and commitment.…”
Section: Value Co-creation and Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…However, customer participation can also lead to negative consequences due to inappropriate participative behaviors or poor interactive mechanism (Bendapudi and Leone 2003;Mustak et al 2013;Hsieh et al 2004;Chan et al 2010;Seiders et al 2015;Ostrom et al 2010). Given these mixed findings, scholars have pointed out the need to explore issues related to the concept of customer participation, such as defining, conceptualizing, measuring, and determining the customer's participative role in service production (Chen and Raab 2014;Mustak et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, this study adopts the definition of customer participation as a customer's behaviors related to the creation and delivery of service offerings (Auh et al 2007;Mustak et al 2013). These behavioral manifestations of customer are confined within the direct interaction or joint sphere of the service process (Grönroos and Voima 2013;Chen and Raab 2014;Gallan et al 2013;Jaakkola and Alexander 2014;Vivek et al 2012).…”
Section: Introductionmentioning
confidence: 99%